Etiopathogenesis of Cholelithiasis and gallbladder cholesterosis - N.Yu. Papshitskaya (Саратовский научно-медицинский журнал, 2009)
The article deals with the contemporary data on etiology and pathogenesis of cholelithiasis, the stages of biliary pathology (motorotonic disturbances of gallbladder and sphincteric apparatus of anhepatic biliary tracts — chronic acalculous cholecystitis — cholelithiasis). The factors, affecting the gallbladder stones formation are described. The problems of pathogenesis of gallbladder cholesterosis are reviewed. The authors come out with an assumption, that disturbances in cholesterol metabolism in the human body play the leading role in the development of this disease.